2015
DOI: 10.1002/btpr.2171
|View full text |Cite
|
Sign up to set email alerts
|

Chemostat production of pediocin SM‐1 by Pediococcus pentosaceus Mees 1934

Abstract: Production of the bacteriocin pediocin SM-1 by Pediococcus pentosaceus Mees 1934 was investigated in pH-controlled batch and chemostat cultures using a complex medium containing glucose, sucrose or fructose. In chemostat cultures operated at 150 rpm, 30°C, 60% dissolved oxygen tension, pH 6.5, and D = 0.148 h(-1) , the pediocin titer reached 185 AU/mL representing an increase of 32% compared with batch cultures in which glucose was used as the carbon source. Pediocin biosynthesis was markedly affected by the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…C. maltaromaticum D0h produced small or no detectable levels of inhibitory compounds in media with initial pH 5.5. This may result from a bacterial strategy to shift energy from biosynthesizing metabolites and translocating them to the external medium, to maintaining internal pH in high H + environments [ 56 , 57 ]. Relatively high pH has been shown to be optimal for the production of bacteriocins by C. maltaromaticum [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. maltaromaticum D0h produced small or no detectable levels of inhibitory compounds in media with initial pH 5.5. This may result from a bacterial strategy to shift energy from biosynthesizing metabolites and translocating them to the external medium, to maintaining internal pH in high H + environments [ 56 , 57 ]. Relatively high pH has been shown to be optimal for the production of bacteriocins by C. maltaromaticum [ 56 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins are small and cationic antimicrobial peptides, ribosomally synthesized by lactic acid bacteria (LAB) (Singh, Ghosh, 2012), with antilisterial activity (Papagianni, Sergelidis, 2015) and many industrial applications (Papagianni, 2003). The industrial importance of LAB is further demonstrated by their status generally recognized as safe (GRAS) (Fan, Song, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They have structural similarities, but different spectrum of antimicrobial activity (Papagianni, Sergelidis, 2015). Pediocins exhibit important technological properties such as thermostability and the capacity of retaining activity at a wide range of pH with bactericidal action especially against Gram-positive food spoilage and pathogenic bacteria; these features make pediocins an important class of biopreservatives (Papagianni, Anastasiadou, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriocins are small and cationic antimicrobial peptides, ribosomally synthesized by lactic acid bacteria (LAB) (Singh, & Ghosh, 2012), with antilisterial activity (Papagianni, & Sergelidis, 2015) and many industrial applications (Papagianni, 2003). The industrial importance of LAB is further evinced by their generally recognized as safe (GRAS) status (Fan, & Song, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several pediocins, the bacteriocins produced by Pediococcus pentosaceus spp., have been characterized (Papagianni, & Anastasiadou, 2009) and they are amongst the most promising bacteriocin in the industry (Turcotte, Lacroix, Kheard, Grignon, & Fliss, 2004) as food preservative (Bharti et al, 2015). They have structural similarities, but different spectrum of antimicrobial activity (Papagianni, & Sergelidis, 2015). Pediocins exhibit important technological properties such as thermostability and retaining of activity at a wide pH range with bactericidal action especially against Gram-positive food spoilage and pathogenic bacteria; these features make pediocins an important class of biopreservatives (Papagianni, & Anastasiadou, 2009).…”
Section: Introductionmentioning
confidence: 99%